Detonations and vapor cloud explosions: Why it matters. (July 2015) - Johnson, D.M.; Tomlin, G.B.; Walker, D.G.
Abstract: The methods used to evaluate the consequences of a vapor cloud explosion assume deflagrations within congested process pipework regions and consequently a significant effort has been invested in developing models to estimate the severity of these deflagrations. Models range from the simpler screening approaches to detailed Computational Fluid Dynamics. There is clear evidence from large scale experiments and incidents that transition from deflagration to detonation is credible and has occurred and it is the contention of this paper that deflagration is only the first stage in many major vapor cloud explosions and that detonation is readily foreseeable. Why does this matter? The methods currently used in the design and location of buildings on and around process sites are based on an incomplete picture of vapor cloud explosions. Whilst this might not have a significant effect in some cases, it is shown that there is the potential to significantly underestimate the explosion hazard. This will result in occupied buildings either being placed in the wrong location or under-designed for the explosion threat, increasing the risks to personnel on these sites. Highlights: We discuss major VCE's and large-scale tests carried out to understand the Buncefield explosion. DDT provides a simple means of explaining the extensive observed following major VCEs. We assess the implications of modeling process facilities without considering DDT.